Pragmatism in Orbis Tertius J. L. Borges's Reading of James - Vargas, Evelyn Teresita (2011)
Many have emphasized Borges's interest in philosophical doctrines throughout his work; less evident was his enduring interest in American pragmatism, particularly James. In the prologues to Pragmatism (1945) and to The Varieties of Religious Experience (1985) Borges depicts James's doctrines in the light of his own lifelong interests in metaphysical questions such as the possibility of freedom and the world as a product of the mind. For Borges these themes reflect James ? pragmatist solution to the problem of the infinite, which gives Borges the framework in which his approach to the author-reader relation can be based.